2018
DOI: 10.3390/mi9070357
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Microturning with Electrochemical Assistance of the Cutting Process

Abstract: The paper investigated an electrochemically-assisted microturning process. Depending on the variant of electrochemical assistance, material can be removed with simultaneous electrochemical and mechanical action or electrochemical assistance can change the conditions of the cutting by changing the mechanical properties of the machined material. The experimental part includes discussion of the study methodology and a comparison of straight turning results in the case of machining 1.4301 stainless steel with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This steel is prone to generating edges on the cutting tool and does not break chips well, especially when the cutting depth falls into the minimal chip thickness zone and the "ploughing effect" becomes prominent. These challenges make machining of 1.4301 steel difficult, especially during microturning and milling processes [38]. Difficulties with the machining of the material prompted an experiment on the impact of milling machining.…”
Section: Introductionmentioning
confidence: 99%
“…This steel is prone to generating edges on the cutting tool and does not break chips well, especially when the cutting depth falls into the minimal chip thickness zone and the "ploughing effect" becomes prominent. These challenges make machining of 1.4301 steel difficult, especially during microturning and milling processes [38]. Difficulties with the machining of the material prompted an experiment on the impact of milling machining.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical mechanical machining combines the electrochemical action and mechanical action, which can efficiently polish the surface of parts and improve the machining accuracy of parts to a certain extent [ 19 , 20 ]. Grabowski et al [ 21 ] found that electrochemical assistance can effectively improve the surface quality in the machining process by comparing the surface quality and precision of 1.4301 stainless steel after turning with or without electrochemical assistance. Ye et al [ 22 ] used a wedged end tube tool for electrochemical milling the deep and narrow groove of GH4169 nickel-based alloy and explored the wedge angle of the cutting tool to improve the electrolyte flowed field and machining quality through simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Precision machining of difficult-to-cut materials can be supported by the electrochemical digestion process in the hybrid machining technology [12].The surfaces of the injection mold, especially the stamp and die surfaces, are exposed to cyclical cooling and heating. These phenomena adversely affect the formation of variable thermal stresses in the material and are the cause of formation of mesh of cracks over time, which ultimately leads to the withdrawal of the mold from further use.…”
Section: Introductionmentioning
confidence: 99%